Strategi Pengajaran Tokoh Agama dalam Menumbuhkan Partisipasi Belajar Jamaah Majelis Taklim At-Taqwa Cibatu, Kabupaten Garut - Hisyam Fadhil; Udin Juhrodin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the teaching strategies employed by religious leaders in enhancing community learning participation through recitation activities at Majelis Taklim At-Taqwa Cibatu, Garut Regency. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation involving religious leaders and members of the majelis taklim. Data analysis was conducted through data reduction, classification, categorization, and thematic interpretation. The results show that the teaching strategies include the use of simple language, contextual delivery of materials, interactive lecture methods, and persuasive approaches toward the congregation. Community participation is influenced by several factors, including religious motivation, spiritual needs, emotional closeness between the congregation and the religious leader, as well as a conducive learning atmosphere. These strategies have proven effective in increasing attendance, active participation, and the sustainability of community involvement in religious activities. This study also highlights that the role of religious leaders is crucial in building a participatory learning environment through communicative and contextually relevant teaching approaches in daily life.